(untitled) (Semiárida, 2022)
Winter cereals are important in the agricultural production of the semi-arid central Pampas region and among them the most widespread is bread wheat (Triticum aestivum L.). In this area, durum wheat (Triticum durum Desf) is not yet cultivated, although it is a crop with good performance for semi-arid zones. Grain and semolina industrial quality of four genotypes of wheat durum cultivated in the Capital department in the province of La Pampa, Argentina, under different nitrogen availability were analyzed. Field work was carried out with four genotypes: Bonaerense INTA Cariló, Ciccio, Buck Cristal and Concadoro and two levels of nitrogen availability in tillering and flowering. There were significant differences among cultivars in all studied characteristics. Nitrogen fertilization increased in some genotypes grain protein concentration and vitreousness. The percent of vitreousness and the yellow pigment content were low, and in the semolina dough there was a high loss of pigment due to the processing associated with the lipoxigenasa activity. Semolina had a high glutenin/gliadin ratio indicating that it would be strong gluten. These results showed that grain and semolina quality attributes were satisfactory although it is necessary to continue generating industrial quality information, evaluating the response of others cultivars particularly, chosen genotypes that allow the optimization of nitrogen fertilization in La Pampa province.